치과용 주조합금의 주조방법에 따른 부식거동 - 최한철(Han-Cheol Choe); 고영무(Yeong-Mu Ko) (Biuletyn Uniejowski, 2004)
The defects of partial denture frameworks are mainly shrinkage porosity, inclusions, micro-crack, particles from investment, and dendritic structure. In order to investigate a good casting condition of partial denture frameworks, the three casting alloys and casting methods were used and detected casting defects were analyzed by using electrochemical methods. Three casting alloys (63Co-27Cr-5.5Mo, 63Ni-16Cr, 63Co-30Cr-5Mo) were prepared for fabricating partial denture frameworks with various casting methods; centrifugal casting (Kerr, USA), high frequency induction casting (Jelenko Eagle, USA), vacuum pressure casting (Bego, Germany). The casting temperature was $1,380^{°}C$ (63Co-27Cr-5.5Mo and 63Ni-16Cr) and $1,420^{°}C$ (63Co-30Cr-5Mo). The casting morphologies were analyzed using FE-SEM and EDX. The corrosion test of the dendritic structure was performed through potentiodynamic method in 0.9% NaCl solutions at $36.5^{°}C$ and corrosion surface was observed using SEM. The defects of partial denture frameworks improved in the order of centrifugal casting, high frequency induction casting, and vacuum pressure casting method, especially, pore defects were found at part of clasp in the case of centrifugal casting method. The structure of casting showed dendritic structure for three casting alloys. In the 63Co-27Cr-5.5Mo and 63Co-30Cr-5Mo, $α$-Co and $ε$-Co phases were identified at matrix and $${γ}$-Ni_2$Cr second phase were shown in 63Ni-16Cr. Also, the corrosion resistance of cast structure increased in the order of vacuum pressure casting, high frequency induction casting, and centrifugal casting method.